Living in the information technology era - Caoili-Tayuan, Ronina R.; Eleazar, Mia V. (Quezon City, Philippines : C & E Publishing Inc., 2019)
IT Application Tools in Business introduces the basic concepts of information technology (IT) applications, tools, and techniques in business environments. It is skillfully arranged to facilitate students' learning and acquisition of technical and applied skills. Hence, it is divided into six units comprised of comprehensive discussionof the following topics: (1) information technology in a business environment, (2) introduction to information systems, (3) emerging technologies for business processes, (4) e-business, e-commerce, and m-commerce, (5) functional and enterprise system, and (6) IT governance, ethical, and security issues in IT. Furthermore, it includes real-world scenarios, case studies, and practical exercises to assess students' level of understanding of the topics. With the book's design, students are allowed the opportunities to evaluate existing systems used by business organization, thereby giving them useful knowledge that they can use in their future profession.
CHAPTER 1. Introduction to information and communication technology -- 2. Computers in our daily life -- 3. The Internet and world wide web -- 4. Information, control and privacy -- 5. IT, Culture and the society -- 6. IT Trends, issues and Challenges.
Includes bibliographical references and index.
Keywords: INFORMATION TECHNOLOGY